2019
DOI: 10.1101/850750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring groundwater microbial communities for natural attenuation potential of micropollutants

Abstract: 14Groundwater is a key water resource, with 45.7% of all drinking water globally being extracted from 15 groundwater. Maintaining good groundwater quality is thus crucial to secure drinking water. 16Micropollutants, such as pesticides, threaten groundwater quality which can be mitigated by 17 biodegradation. Hence, exploring microbial communities in aquifers used for drinking water 18 production is essential for understanding micropollutants biodegradation capacity. This study aimed 19 at understanding the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 41 publications
2
7
1
Order By: Relevance
“…Half of the wells had oxygen concentrations higher than 1 mg/L (i.e., 16, 17, 25, 26, 27) (Table 2). The fact that there is oxygen in some of the shallow depths sampled waters show that not all of the monitoring wells are completely anaerobic as expected based on previous field studies ( Aldas-Vargas et al, 2019). Additionally, in two wells (i.e., shallow depths (Table 2).…”
Section: Geochemical Characterization Of the Aquifersupporting
confidence: 77%
See 4 more Smart Citations
“…Half of the wells had oxygen concentrations higher than 1 mg/L (i.e., 16, 17, 25, 26, 27) (Table 2). The fact that there is oxygen in some of the shallow depths sampled waters show that not all of the monitoring wells are completely anaerobic as expected based on previous field studies ( Aldas-Vargas et al, 2019). Additionally, in two wells (i.e., shallow depths (Table 2).…”
Section: Geochemical Characterization Of the Aquifersupporting
confidence: 77%
“…Overall, the main significant explanatory variables for differences between microbial communities are electron acceptors. In a similar field study, it was already reported that electron acceptors are among the most influential factors shaping microbial communities even in the presence of pesticides (Aldas-Vargas et al, 2019). However, in the present study, pH showed to be the most significant environmental factor influencing aquifer microbial communities (Table 3).…”
Section: Geochemical Characterization Of the Aquifercontrasting
confidence: 41%
See 3 more Smart Citations